Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/jp0487657
|View full text |Cite
|
Sign up to set email alerts
|

Ground and Low-Lying States of Cu2+−H2O. A Difficult Case for Density Functional Methods

Abstract: The ground and low-lying states of Cu2+−H2O have been studied using different density functional and post-Hartree−Fock methods. CCSD(T) results indicate that Cu2+−H2O has C 2 v symmetry and that the ground electronic state is a 2A1 state. At this level of theory the relative order of the electronic states is 2A1 < 2B1 < 2B2 < 2A2. However, density functional results show that the relative stabilities of these states vary depending on the degree of mixing of exact Hartree−Fock (HF) and density functional (DF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 76 publications
6
89
0
Order By: Relevance
“…The application of the B3LYP method to metal ion-water systems has proved a reasonable success. [52][53][54][55] For open-shell Cu 2+ -ligand systems with low coordination numbers (n ) 1, 2) it has been reported [56][57][58] that B3LYP binding energies are overestimated compared to CCSD(T) results. However, the B3LYP relative energies for systems with similar spin density distribution are in good agreement with those determined by highly correlated electronic structure methods.…”
Section: Methodsmentioning
confidence: 99%
“…The application of the B3LYP method to metal ion-water systems has proved a reasonable success. [52][53][54][55] For open-shell Cu 2+ -ligand systems with low coordination numbers (n ) 1, 2) it has been reported [56][57][58] that B3LYP binding energies are overestimated compared to CCSD(T) results. However, the B3LYP relative energies for systems with similar spin density distribution are in good agreement with those determined by highly correlated electronic structure methods.…”
Section: Methodsmentioning
confidence: 99%
“…Methods based on the density functional theory (DFT) have been shown to be costeffective and have been used to study a wide variety of closedshell systems with great accuracy (Koch & Holthausen 2001;Sousa et al 2007;Sholl & Steckel 2009). However, for openshell systems, calculations carried out by some of us have demonstrated that functionals with a higher percentage of exact exchange, such as BHLYP, provide results in better agreement with those from the highly correlated CCSD(T) method (Poater et al 2004;Rimola et al 2006Rimola et al , 2008. This is because functionals based on the generalized gradient approach (GGA) or hybrid approaches with low percentages of exact exchange such as B3LYP (20%) tend to overstabilize electron-delocalized situations as a result of the self-interaction error (Sodupe et al 1999).…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…34 We have used the B3LYP 35 hybrid exchange-correlation functional, which provides an accurate and computationally balanced method that is able to correct the excess of covalence frequently found in Cu 2+ compounds when using local (LDA) or semilocal (GGA) density functionals. 36 The Kohn-Sham orbitals were described using a Slater-function basis set of triple-ξ plus polarization quality for all ions and atoms in the complex and double-ξ for all ions outside of it. Geometry optimizations were carried out, including all degrees of freedom for the ions in the complex, while the external layers of the cluster were fixed to match the perfect lattice positions.…”
Section: Computational Detailsmentioning
confidence: 99%